Editorial comment on “Reimplantation of the upper lobe bronchus after lower sleeve lobectomy or bilobectomy: long-term results” by Maurizi et al. - Ludwig, Corinna (Journal of Thoracic Disease, 2018)
The advantage of sleeve lobectomy over pneumonectomy in terms of postoperative morbidity and mortality in centrally located lung cancer is well established (1-5). The incidence of sleeve procedures still varies largely world-wide. In the above mentioned article by Maurizi et al. long-term results after complex tracheobronchial reconstruction are presented together with technical aspects (6).